Clinical and PSG Characteristics of Children with Mild OSA and Respiratory Events Terminated Predominantly with Arousal - Yunxiao Wu; Li Zheng; Panting Wu; Yufen Tang; Zhifei Xu; Xin Ni (Canadian Respiratory Journal)
Objective. To analyze the clinical and polysomnographic characteristics in children with mild OSA and respiratory events terminated predominantly with arousal. Methods. Children aged 3–10 yrs who had mild obstructive sleep apnea (OSA) were enrolled. All children underwent polysomnography, and patients’ data were collected by using sleep-related breathing disorders (SRBD) questionnaire and OSA-18 quality of life questionnaire. Results. In total, five hundred and seventy-seven children were eligible. Children in arousal predominant group were younger and showed a lower rate of male and obesity. Compared with that of the nonarousal predominant group, the total arousal index, arousal index related to respiratory event, the percentage of NREM stage 1 (N1%), the fraction of respiratory events that were hypopnea, and the mean and minimum oxygen saturation in the arousal predominant group were significantly greater. The percentage of NREM stage 3 (N%), index of obstructive, central, mixed apnea, the fraction of respiratory events that were obstructive, and central and mixed apnea were significantly lower in arousal predominant group. Conclusion. Children with mild OSA in the arousal predominant group had specific characteristics, including younger age, lower rate of male and obesity, worse sleep architecture, higher rates of hypopnea events, and better oxygenation. This trial is registered with NCT02447614.